Efficient numerical analysis of focal plane antennas for the SKA and the MeerKAT - Ludick, Daniel Jacobus (Stellenbosch : University of Stellenbosch, 2010)
Thesis (MScEng (Electrical and Electronic Engineering))--University of Stellenbosch, 2010.